2008
DOI: 10.1146/annurev.publhealth.29.020907.090934
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Care Systems in Increased Tobacco Cessation

Abstract: Health care delivery systems are critical components of tobacco cessation efforts. This review summarizes recent evidence in sup-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 75 publications
(79 reference statements)
2
67
0
6
Order By: Relevance
“…National data show an increase in reported advice to quit smoking from a health-care provider from 40% in the mid-1990s to 61% in the mid-2000s, with similar increases across racial and ethnic groups. 76,77 The 2006 Healthcare Effectiveness Data and Information Set (HEDIS) report, from the National Committee for Quality Assurance, showed 71% of smokers or recent quitters who had private insurance received advice to quit smoking from their health-care provider, and 39% reported discussing smoking cessation strategies; corresponding rates among Medicaid recipients were lower at 66% and 34%, respectively. 78 However, the use of evidence-based treatments in quit attempts remains low, with an estimated 22% of smokers trying to quit by using cessation aids.…”
Section: Smoke-free Initiatives To Reduce Exposure To Secondhand Smokementioning
confidence: 99%
See 2 more Smart Citations
“…National data show an increase in reported advice to quit smoking from a health-care provider from 40% in the mid-1990s to 61% in the mid-2000s, with similar increases across racial and ethnic groups. 76,77 The 2006 Healthcare Effectiveness Data and Information Set (HEDIS) report, from the National Committee for Quality Assurance, showed 71% of smokers or recent quitters who had private insurance received advice to quit smoking from their health-care provider, and 39% reported discussing smoking cessation strategies; corresponding rates among Medicaid recipients were lower at 66% and 34%, respectively. 78 However, the use of evidence-based treatments in quit attempts remains low, with an estimated 22% of smokers trying to quit by using cessation aids.…”
Section: Smoke-free Initiatives To Reduce Exposure To Secondhand Smokementioning
confidence: 99%
“…However, even insured smokers may bear a significant portion of the cost of pharmacotherapy because of deductibles and copayments or, in some cases, because of noncoverage. 76,80 In some cases, coverage is extended only to certain groups of smokers. For example, Medicare covers smoking-cessation counseling and pharmacotherapy (excluding over-the-counter treatment) for seniors with tobacco-related illnesses, and in some states, the Medicaid program covers treatments only for pregnant women.…”
Section: Smoke-free Initiatives To Reduce Exposure To Secondhand Smokementioning
confidence: 99%
See 1 more Smart Citation
“…Effective smoking cessation programs have the potential to dramatically decrease health care utilization and costs [41][42][43][44]. A cost-benefit analysis found that the ratio of benefits to cost varies from US$0.80 to US$2.40 saved per dollar spent on smoking cessation programs, depending upon the type of intervention [45].…”
Section: Original Researchmentioning
confidence: 99%
“…Behavioral interventions, such as smoking cessation strategies, increasingly rest upon a solid body of research evidence demonstrating their efficacy. Yet translational behavioral medicine will not become a reality until we can ensure that these evidence-based interventions move from the research realm into practice, and that they are, in actuality, (a) implemented in clinical practice of behavioral medicine, with sufficient quality to benefit individual patients, and (b) incorporated into the knowledge base supporting behavioral medicine, such that they inform care for relevant populations [6][7][8][9].…”
Section: Growth In Data Availabilitymentioning
confidence: 99%